PENGARUH KARAKTERISTIK SOSIAL EKONOMI PETERNAK TERHADAP ADOPSI SISTEM BAGI HASIL (TESENG) DI DESA MATTIROWALIE, LIBURENG KABUPATEN BONE - Syahdar Baba; Rahmayanti Rahmayanti; St. Rohani; Sitti Sohrah (Jurnal Ilmu dan Teknologi Peternakan, 2021)
For small-scale beef cattle farmers, capital is one of the main inhibiting factors in developing their farming. Teseng is one of the local wisdom which is a solution for providing capital for small-scale farmers. This study aims to determine the effect of the socio-economic characteristics of breeders on the adoption of Teseng. The research was conducted in Mattirowalie Village, Libureng District, Bone Regency, which is one of the areas in the development of the Teseng system. The number of samples was 76 breeders consisting of 61 farmers who did not adopt Teseng and 15 breeders who adopt Teseng. The independent variable consists of perceptions of capital availability (X1), land area (X2), number of livestock (X3) and age of farmers (X4). The dependent variable is the adoption of Teseng. The regression model used was logistic regression because the dependent variable was a dichotomous variable (1 for adoption and 0 for no adoption of Teseng). The results showed that the factors that influenced the adoption of Teseng were land area (P<0.01) and the number of livestock (P<0.05). Perception, age and number of families did not have a significant effect on Teseng adoption. To increase the adoption of Teseng, the ability of breeders to provide feed both from the existing land and from the provision of alternative feed needs to be developed.